Fault Detection for Low Voltage System in Electric Vehicle - Muhammad Anwar Sadat Faidar; Kamlasi, Dava; Yusivar, Feri (Universitas Indonesia, 2023)
With the rapid development of the electric vehicle ecosystem, there are concerns about the electrical safety of electric vehicles. This concern is caused by the problems with electric vehicles, which cannot be used when not used for a long time. This problem is caused by a low voltage rating that is not available when the electric vehicle is in that condition. In this study, an algorithm is proposed to support safety for the availability of low-voltage electrical energy, when electric vehicles are in use or not in use. The results of this research indicate that the created algorithm can provide safety for the availability of low voltage level electrical energy, by adjusting the lead-acid battery charging procedure, monitoring the low voltage level while it not in use, and making existing electric vehicles unable to move as long as problems with the low voltage level charging system cannot be resolved.